2016
DOI: 10.3109/14764172.2015.1052514
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline for the treatment of cutaneous silicone granulomas: A case report

Abstract: Silicone oil injections are often used for soft tissue augmentation and local and general adverse effects occurring from a few months to 15 years after injection have been reported. Here, we present a case of delayed granuloma formation due to liquid injectable silicone with large extent of involvement, which precluded surgical removal. Our patient was successfully treated with minocycline, considering its anti-inflammatory, immunomodulating and antigranulomatous properties. This case presents minocycline mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…First is the observation that doxycycline may be able to hinder granuloma formation (in vitro model) via inhibition of protein kinase C, with one study finding a dose‐dependent relationship in this effect . Furthermore, there have been some case reports that minocycline has been effective in treating patients with silicone‐induced granulomas …”
Section: Methods and Resultsmentioning
confidence: 99%
“…First is the observation that doxycycline may be able to hinder granuloma formation (in vitro model) via inhibition of protein kinase C, with one study finding a dose‐dependent relationship in this effect . Furthermore, there have been some case reports that minocycline has been effective in treating patients with silicone‐induced granulomas …”
Section: Methods and Resultsmentioning
confidence: 99%
“…The more common treatments include systemic and local steroids, 3 minocycline, 16,37 5-fluorouracil, 44 isotretinoin 45 and, for localized granuloma formation, surgical resection. While success has been achieved with steroids, relapse often occurs after a steroid taper.…”
Section: Discussionmentioning
confidence: 99%
“…In another case in which surgical involvement was precluded, Crocco et al reported successful treatment with systemic minocycline monotherapy. 37 Another highly interesting case demonstrating the delayed onset of silicone granuloma formation was described in 2014 by Eun et al 38 They reported the case of a 62-year-old woman in South Korea who had presented with a disfigured nose. The disfiguration involved thickening and lichenification of the nasal root and the upper two-thirds of the nose, which resulted in an elephant trunk-like appearance.…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…4,5 Several reports document the potential vulnerary effects of doxycycline in the eye, 6 in the oral cavity, 7,8 and following hernia repair 9 and imply an ability to reduce skin scarring. [10][11][12] Here, we report that a one-time local dose of 3.90 mM doxycycline (2 mg/mL) within 12 hours of injury significantly reduces scar thickness without compromising tensile strength. The same effect cannot be achieved by oral dosing.…”
mentioning
confidence: 85%